Material and Electrochemical Characterization of Tetrapropylammonium Manganese Oxide Thin Films as Novel Electrode Materials for Electrochemical Capacitors - Chin, S.F.; Pang, S.C.; Anderson, Marc A. (The Electrochemical Society, Inc., 2002)
Stable colloidal tetrapropylammonium manganese oxide ~TPA-MO! was formed by the reduction of tetrapropylammonium permanganate with 2-butanol at room temperature. Thin films of TPA-MO were prepared using the sol-gel process by dip-coating directly onto clean nickel foils followed by heat-treatment under controlled conditions. The microstructure evolution of TPA-MO films at various calcination temperatures was characterized using Brunauer-Emmett-Teller method, X-ray diffraction, and scanning electron microscopy. The performance of these films as supercapacitors was evaluated using cyclic voltammetry in various aqueous electrolytes. These thin films exhibited excellent capacitive behavior with a specific capacitance of 720 F/g. These films also showed good reversibility and cycling stability, losing little more than 20% of their charge capacity after 1500 cycles.